Hubungan Fathering dan Emotional Maturity dengan Intimacy dalam Menjalin Hubungan Romantis pada Mahasiswi - Hadisawa, Sisy Tamara; Nurhadianti, Rr. Dini Diah (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
This article aims to determine the relationship between fathering and emotional maturity with intimacy in having a romantic relationship with female students at the Faculty of Psychology, X University. The subjects in this study were 104 female students aged 18 to 25 years in which the data collection method was using accidental sampling technique. Measuring instruments used were intimacy scale (14 items, α = 0.814), fathering scale (16 items, α = 0.924), and emotional maturity scale (22 items, α = 0.760). Based on the results of data analysis using IBM SPSS Statistics 22 with bivariate correlation techniques, there is a no significant relationship between fathering with intimacy in having a romantic relationship of r = 0.090 and p = 0.362; (p) > 0.05, and there is a significant positive relationship between emotional maturity with intimacy in having a romantic relationship of r = 0.354 and p = 0.000; (p) < 0.05. Furthermore, the results of data analysis with multivariate correlation techniques obtained correlation coefficient R = 0.361, R2 = 0.130, and p = 0.001; (p) < 0.05 . This states that there is a relationship between fathering and emotional maturity with intimacy in having a romantic relationship with female students at the Faculty of Psychology, X University